The Peculiarities of the System of Ukraine’s Law Enforcement Bodies in the Field of Cybercrime Resistance. - Krainii, Pavlo; Toronchuk, Ivan (My University, 2021)
Today’s rapid development of information technologies has affected all spheres of public life. There are more and more reports in the media on the disclosure of criminal offenses in the field of telecommunications, Internet services, banking institutions, payment systems, etc. To set up a perfect, efficient, professional and high-tech system of special law enforcement agencies that will be able to counter the threats of cybercrime is one of the most significant tasks in developing the defense system of any state. The experience of the past few years has clearly shown that certain manipulations, carried out by a group of cybercriminals with the help of special equipment worth several thousand dollars can cause damages that may reach millions of dollars. Having been at war with the Russian Federation for seven years, Ukraine is still trying to elaborate an effective system of law enforcement agencies that can really ensure reliable protection of the rights and freedoms of its citizens in cyberspace.
Keywords: Cybercrime Resistance; Ukraine’s Law Enforcement Bodies; cyber security